Exome sequencing for prenatal diagnosis of fetuses with sonographic abnormalities. (11th September 2015) - Drury, Suzanne; Williams, Hywel; Trump, Natalie; Boustred, Christopher; GOSGene; Lench, Nicholas; Scott, Richard H.; Chitty, Lyn S.; Chitty, Lyn S.; Bianchi, Diana W.
Abstract Objective In the absence of aneuploidy or other pathogenic cytogenetic abnormality, fetuses with increased nuchal translucency (NT ≥ 3.5 mm) and/or other sonographic abnormalities have a greater incidence of genetic syndromes, but defining the underlying pathology can be challenging. Here, we investigate the value of whole exome sequencing in fetuses with sonographic abnormalities but normal microarray analysis. Method Whole exome sequencing was performed on DNA extracted from chorionic villi or amniocytes in 24 fetuses with unexplained ultrasound findings. In the first 14 cases sequencing was initially performed on fetal DNA only. For the remaining 10, the trio of fetus, mother and father was sequenced simultaneously. Results In 21% (5/24) cases, exome sequencing provided definitive diagnoses (Milroy disease, hypophosphatasia, achondrogenesis type 2, Freeman–Sheldon syndrome and Baraitser–Winter Syndrome). In a further case, a plausible diagnosis of orofaciodigital syndrome type 6 was made. In two others, a single mutation in an autosomal recessive gene was identified, but incomplete sequencing coverage precluded exclusion of the presence of a second mutation. Conclusion Whole exome sequencing improves prenatal diagnosis in euploid fetuses with abnormal ultrasound scans. In order to expedite interpretation of results, trio sequencing should be employed, but interpretation can still be compromised by incomplete coverage of relevant genes. © 2015 John Wiley & Sons, Ltd.